Evidence of the involvement of Xylella fastidiosa in the occurrence of walnut leaf scorch in Xinjiang, China - Guo, Tong (Plant disease, 2024)
Walnut (Juglans regia Linn.) leaf scorch (WLS) was first reported in 2012 in Hotan, Xinjiang, China (Zhang et al., 2012). Initially, brown spots appear at the apex of the leaflets with slight shrinking. These spots spread inward along the leaf margins in a flame-like pattern. The scorched areas curl inward with a yellow halo. No powdery or bacterial signs were observed on the leaf surface. In severe cases, the leaves dried up and shrank, affecting the entire tree. However, new leaves did not show any signs of scorching. We collected 300 symptomatic leaf samples from 10-12 year-old trees of the susceptible WLS species Wen185, located in Daryaboyi (40°72'N, 80°49'E), Xakal (40°69'N, 80°52'E), and Karatal (40°73'N, 80°39'E) for X. fastidiosa PCR detection analysis. X. fastidiosa was detected in asymptomatic leaves of trees with severe WLS, as well as in asymptomatic leaves of trees exhibiting mild WLS symptoms, and it was even found in asymptomatic leaves of trees without any WLS symptoms.To isolate X. fastidiosa, walnut leaves with petioles were disinfected with 3% bleach for 10 minutes, followed by four washes in autoclaved deionized water. The midrib and petiole of the leaf were cut off with a sterile blade, and a 2 mm to 3 mm section was excised. Then, the cut ends were squeezed with a pair of pliers, and the sap was blotted onto Periwinkle Wilt (PW) plates (Davis et al. 1983). The plates were sealed with parafilm and incubated at 28°C in the dark, with daily observations for the development of individual colonies. The sap collected from 5 out of 20 leaf samples with scorch symptoms and from 20 leaves without symptoms never showed bacterial growth in PW.. Six colonies were tested and confirmed positive for X. fastidiosa using the RST31 and RST33 primer pair (Minsavage et al., 1994). The uploaded sequence accession numbers are PP871340-PP871342. Blast analysis of Multilocus Sequence Typing (MLST) sequences from the isolated strain using the X. fastidiosa MLST Database (http://pubmlst.org/xfastidiosa) revealed a perfect match with sequences of alleles leuA_3, petC_3, malF_, cysG_3, holC_4, nuoL_3, and gltT_3 (PP871343-PP871349). Using MEGA software to concatenate the MLST single gene fragments and construct a ML multi-gene fragment phylogenetic tree through Maximum Likelihood (ML) analysis, the bacterium was identified as X. fastidiosa subsp. multiplex To fulfill Koch's postulates, a purified colony from the PW plate was suspended in 500 μL of deionized water at 1×10^8 CFU·mL-1. A sterilized 5 ml medical needle was used to prick a small hole on the main branch, 5 cm from the base, of three-year-old walnut seedlings, and the bacterial solution was injected into the small hole. Three biological replicates were performed for each treatment (5 μL and 10 μL of bacterial solution, deionized water), and the experiment was repeated three times. Scorching symptoms were observed three months after inoculation in 11 out of the 15 seedlings inoculated with a 10 μL bacterial solution, and isolation of X. fastidiosa occurred in leaf samples from 5 of these seedlings, completing Koch's postulates. Walnut seedlings with water stayed asymptomatic, PCR negative. To our knowledge, X. fastidiosa has been found infecting grapes (Chu, 2001) in Shaanxi, China and pears (Su et al., 2016) in Taiwan, China. This is the first report of X. fastidiosa involvement in WLS in China. Further research on the occurrence of the disease will help prevent the spread of the disease